PERLINDUNGAN HUKUM TERHADAP HAK PEKERJA OUTSOURCING BERDASARKAN PUTUSAN MK NOMOR 27/PUU-IX/2011 - Wati, Dwi Liza; Haryono, Dodi; ', Junaidi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Climate of increasingly tough competition makes the company seeks to improve efficiency of production costs (cost of production). Workers with a system of outsourcing in practice that outsourced workers are given only 1 hour resting of 12 hours of work, especially security, and is not given for a period of vacation time that has reached 1 (one) year or more. If the outsourced workers will ask leave of absence, the submission will not be considered on leave but permission kerja.Tujuan writing this essay, namely: First, to determine the legal reasoning of the Constitutional Court decision No. 27 / PUU-IX / 2011 in the case of petition for judicial review of Law No. 13 of 2003 on Employment of the Constitution of 1945. Second, to determine the legal implications of the decision of the Constitutional Court Number 27 / PUU-IX / 2011 on the legal protection for outsourced workers in Law No. 13 Year 2003 on Manpower.This research is descriptive analysis of legal research because of the results of this study are expected to be obtained data describing thoroughly, clearly and systematically on the Legal Protection Against Workers in Labor Agreement With Outsourcing System in Indonesia. Data source is the primary legal materials, secondary law, and tertiary legal materials. Data collection for the study of normative law used literature study method or documentary studies. Was analyzed qualitatively analyzed the data by not using statistics or mathematics, or the like.From the results of this study, there are two main things that can be inferred First, through the decision of the Constitutional Court provides protection to workers / labor outsourcing, in this decision reaffirms the rule against contract workers or workers must follow existing regulations by adding a guarantee continuity of workers in the contract. Decision of this Court is protective labor rights / labor, then the government needs strict monitoring of the implementation of outsourcing.Keywords: Protection Law, Outsourcing Workers' Rights, Constitutional Court.